AB1470-HPR Study for complete implementation of T2T for all RA patients. (23rd January 2014) - Funahashi, K.; Matsubara, T.; Ida, T.; Kashiwagi, I.; Ueda, T.; Koizumi, S.
Abstract : Background: According to our survey conducted on RA patients last year, it was suggested that although implementation of T2T has been realized on patients treated with biological products, for those who are not, T2T education is inadequate. In Japan, regular healthcare workers are not given opportunities for T2T training except for those RA care nurses and RA specialists who have received special training domestically or abroad. Objectives: We examined ways in which we could establish a system in our hospital for all RA patients to receive T2T whether using biologics or not. Methods: First, T2T workshops were given to all the healthcare workers at our hospital. After a 30 minute lecture and slideshow about RA classification standards, drugs, the concept of T2T, and patients' thoughts and concerns, we checked the participants' level of understanding for those topics on a scale of one to three. To further the study, we conducted a survey among the participants soliciting their opinions about how to realize complete T2T implementation regardless of treatment. Based on the results of the survey we considered making an RA handbook to distribute all RA patients in our facility. Results: Among 57 participants (90% of all our medical staff), 70% were nurses, half of whom were in their thirties. Seventy-seven percent of the participants thought the workshop was useful and 98% understood the basics of the lecture. Ninety-three percent answered "Yes" to the question about patients knowing about T2T, and if so, if they thought their prognosis would change. For full implementation of T2T, 81% thought "continuing education for patients" is important, followed by "regular education for allied health professionals" (66%), "clarifying treatment goals for advanced RA patients" (59%), "making and distributing RA handbooks" (57%), and "altering the treatment course set by doctors" (54%). To an open question about T2T, answers were "need to have exclusive RA care nurses", "agreement on the treatment course among doctors" and "extended care to elderly patients and those without enough information". Thereafter to examine the concept of making handbooks and their contents, a session was held in which we discussed 3 types of checklists for the handbooks; one for patient background including history of diseases, treatment, and adverse events and the others for assessments done by patients themselves every 3 month and treatment goals that should be decided with doctors respectively. Along with those checklists, it is suggested that the book have a record for health checks (including cancer screening). Also we considered the possibility of hiring excusive RA care nurses for our patients. Conclusions: In Japan, doctors usually can't spare enough time for counseling with patient due to overloaded schedules. The reason patients treated with biologics are well educated about T2T is because they've had more opportunity for one to one counseling with medical staff. To do the same for every patient, help from allied health professionals is indispensable. In promoting T2T education, we believe it is very important to introduce one to one counseling for each patient regardless of their treatment path and distribute RA handbooks to them. Disclosure of Interest: None Declared